The Effect of Burrs on the Shear Capacity of Bearing Connections - Zwerneman, F.J.; Saleh, Y. (Engineering Journal, 1996)
Research was conducted to assess the effect of burrs on the shear capacity of bolted connections. This paper describes results relevant to the performance of bearing connections. Forty-five specimens were tested with burr heights ranging from 0 to 0.176 inches. Results show that the presence of burrs in bearing connections does not significantly reduce the shear capacity of the connection.